Multiple Gate Delay Tracking Structures for GNSS Signals and Their Evaluation with Simulink, SystemC, and VHDL. (23rd March 2008) - Hurskainen, Heikki; Simona Lohan, Elena; Hu, Xuan; Raasakka, Jussi; Nurmi, Jari
Abstract : Accurate delay tracking in multipath environments is one of the prerequisites of modern GNSS receivers. Several solutions have been proposed in the literature, both feedback and feedforward. However, this topic is still under active research focus, especially for mass-market receivers, where selection of lowcomplexity, nonpatented methods is preferred. Among the most encountered delay tracking structures implemented in today's receivers, we have the narrow correlator and the double-delta correlators. Both are heavily covered by various patents. The purpose of this paper is to introduce a new, generic structure, called multiple gate delay (MGD) structure, which covers also the patented correlators but offers much more flexibility in the design process. We show how the design parameters of such a structure can be optimized, we argue the performance of this structure via detailed simulation results based on various simulators, such as Matlab/Simulink-based tool, GRANADA, and we test the implementation feasibility of MGD structures on actual devices, via SystemC and FPGA prototyping. One of the main advantages of the proposed structure is its high degree of flexibility, which allows the designer to choose among, to the authors' knowledge, nonpatented solutions with delay tracking accuracy comparable with that of the current state-of-art trackers.